Geochemical and geomechanical alteration of siliciclastic reservoir rock by supercritical CO2-saturated brine formed during geological carbon sequestration. (September 2019) - Fuchs, Samantha J.; Espinoza, D. Nicholas; Lopano, Christina L.; Akono, Ange-Therese; Werth, Charles J.
Highlights: Cementing clays separated from grains after exposure to scCO2 -saturated brine. Clay cement weakening reduced sandstone fracture toughness. Porosity increased from 8% to 15% after 8 weeks in acidified brine. Alterations were observed in N2 -saturated conditions, but not the same extent. Abstract: Geologic carbon sequestration (GCS) is an approach for storing CO2 and mitigating greenhouse gas emissions. During GCS, carbon dioxide dissolves into pore water, resulting in a low-pH brine that can react with reservoir rock minerals. This work evaluates the effects of geochemical reactions on geomechanical integrity of representative siliciclastic reservoir samples obtained from the Mt. Simon formation. Rock samples were aged 4 or 8 weeks in CO2 -saturated brine under reservoir conditions, and in N2 -saturated brine as a control. Post-aging, CT scans revealed more extensive micro-fracture development along horizontal bedding planes at grain edges in CO2 versus N2 -aged samples. Digital analysis of CO2 -aged samples showed porosity increase from 8.1% to 15.8%. Scanning electron microscopy revealed the loss of clay cementation, greater exposure of quartz and K-feldspar grains, and apparent surface roughening (confirmed by laser profilometry) in CO2 -aged samples, but not in N2 -aged samples. Fracture toughness as evaluated by scratch testing was reduced by 32.1% after 4 weeks in scCO2 -saturated brine and 69.5% after 8 weeks. The primary reason for weakening appears to be detachment of clays from quartz and feldspar grain surfaces, resulting in weakening of the rock matrix. Rock weakening may alter the geomechanical stability of storage formations.